PENGALAMAN NILAI ESTETIS MENURUT DEWITT HENRY PARKER DAN RELEVANSINYA DENGAN PENGEMBANGAN KARAKTER BANGSA INDONESIA - , MOSES GLORINO RUMAMBO PANDIN; , Dr.Sumartono, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Art study is a part of axiology. The aim of research is to study DeWitt Henry Parkerâs ideas of aesthetic, aesthetics experience and its relevance. The concepts are centralized in the metaphysicâs value of experience. These reflections anchored in idealism and empiricism of American philosopherâs repertoire. The researchâ purpose would like to reveal the concepts of aesthetics and aesthetics experience according to Parker. This investigation also will analyze the construct of experience of aesthetics value and find out its significance to build Indonesian national character. A qualitative research method is using with a library research model. The research process begins to classify the ideas of Parkers reflection as main collection and secondary data of other thinkers. Secondly the data are processed. The results data are analyzed by describing, interpreting, using internal coherence and heuristics approach in finding the idea of Parker. The results found the concept of aesthetics and experience of aesthetics value based on Parkerâs metaphysics. Aesthetics is an expression or experience. The principle of experience of aesthetic value is unity of subject-object, unity feelings, thoughts, pleasure and personal and universal quality. The principle is applied into criteria of aesthetic value experience. Parker's concept reflects the rational idealism and empiricism patterned by psycho-voluntarism. The significant relevance of the idea best applied to develop the Indonesian national character. The implementation of Parkerâs ideas is anchored in the principles of unity and balance of Pancasila. Through the experience of aesthetics value principle, people do awaken, develop the feeling and taste of Indonesian national character in education field.